Prevención interdisciplinaria en el desarrollo de las habilidades básicas para el aprendizaje de estudiantes con necesidades educativas especiales. - Martínez Ortiz, Martha (2021)
Attention to special educational needs requires the support of an interdisciplinary team that does not assign full responsibility to the teacher, but allows the educational process to be supported so that it is more advantageous. The present study aimed to describe how interdisciplinary prevention affects the development of basic skills for learning in students with special educational needs. To carry out the research, variables such as basic skills for learning from a neuropsychological and psycho pedagogical approach, early care as part of a preventive process, the intervention of professional teams in which interdisciplinary stands out, were analyzed........